2011
DOI: 10.1108/14691931111181706
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual capital and firm performance in Australia

Abstract: This study examines the effect intellectual capital (IC) has on firm performance using a sample of Australian companies listed between 2004 and 2008. IC is measured using Pulic's Value Added Intellectual Coefficient (VAIC) and its components and both a direct and a moderating relationship between VAIC and performance are analysed. The results suggest that there is a direct relationship between IC and performance of Australian publicly listed firms, particularly with capital employed efficiency and to a lesser … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

63
448
7
30

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 411 publications
(548 citation statements)
references
References 41 publications
63
448
7
30
Order By: Relevance
“…According to [55], this so called new economy, also known as the knowledge economy, has shifted attention to the intangible assets possessed by organizations and how they are managed. This is supported by [56] who stated that for organizations operating in this new economy, intellectual not physical capital is considered to be an organization's most prized asset. The reason why intellectual capital is considered valuable relates to the fact that intangible assets are more important than tangible assets [57].…”
Section: Intellectual Capital (Ic)mentioning
confidence: 65%
“…According to [55], this so called new economy, also known as the knowledge economy, has shifted attention to the intangible assets possessed by organizations and how they are managed. This is supported by [56] who stated that for organizations operating in this new economy, intellectual not physical capital is considered to be an organization's most prized asset. The reason why intellectual capital is considered valuable relates to the fact that intangible assets are more important than tangible assets [57].…”
Section: Intellectual Capital (Ic)mentioning
confidence: 65%
“…The study indicated that human capital is most important component of intellectual capital and all three dimensions as proposed by VAIC are significant explanatory variables for profitability as measured by return in asset. Clarke, Seng and Whiting (2011) conducted same type of study in Australian business context. Using VAIC model as proposed by Pulic, the study found a direct impact of intellectual capital and firm performance and dimensions of capital employed efficiency and to a lesser extent human capital efficiency are important in this regard.…”
Section: International Journal Of Accounting and Financial Reportingmentioning
confidence: 99%
“…This is because, VAIC technique is distinctive due to easy availability of audited financial data and it is also less criticized model compared to other models as well as the most recent model among them. Additionally, VAIC has been adopted in several studies to examine the relationship between IC and firms performance (Clarke et al, 2011;Maditinos et al, 2011;AnneLaure and Nick, 2013).…”
Section: Measures Of Variablesmentioning
confidence: 99%